Thermal and exergy optimization of a nanofluid-based direct absorption solar collector. (June 2017) - Gorji, Tahereh B.; Ranjbar, A.A.
Abstract: An experimental study on a nanofluid-based direct absorption solar collector (DASC) was carried out to analyze the effect of its operating conditions on the thermal performance of the collector. Graphite, magnetite and silver nanoparticles dispersed in de-ionized water were used as the heat transfer fluids. Experiments were conducted for various nanoparticle volume fractions of ( 5 < f v < 40 ppm); volumetric flow rates ( 5 < Q < 10 ml/min) and incident radiation fluxes ( 600 < G T < 1000 W/m 2 ) based on Box-Behnken experimental design feature. The acquired data were analyzed according to response surface methodology (RSM) and the relation between the input parameters and responses (thermal and exergy efficiencies) for each nanofluid was expressed by response surface functions. The results show that among nanofluids, magnetite dispersions gained the highest thermal and exergy efficiencies; followed by graphite and silver nanofluids, respectively. Also, optimum operating conditions for each nanofluid revealed that in the given design range, the maximum thermal and exergy efficiencies occurred at f v = 40 ppm, Q = 10 ml/min and G T = 884 W/m 2 for magnetite; f v = 40 ppm, Q = 10 ml/min and G T = 884 W/m 2 for graphite and f v = 38.6, Q = 10 ml/min and G T = 826 W/m 2 for silver nanofluids. Highlights: An experimental investigation on a direct absorption solar collector (DASC) exploiting functionalized graphite, magnetite and silver nanoparticles dispersed in water nanofluids has been conducted. Response surface methodology with Box-Behnken experimental design approach was applied to arrange the experiments and analyze the results. Derringer and Suich's optimization technique was applied to optimize the operating conditions of the collector.